Alpha-defensins increase NTHi binding but not engulfment by the macrophages enhancing airway inflammation in Alpha-1 antitrypsin deficiency - Lee, Jungnam; Mohammad, Naweed; Han, Kyudong; Flagg-Dowie, Tammy; Magallon, Maria; Brantly, Mark L.; Serban, Karina A. (Frontiers in Immunology, 2025)
Neutrophilic inflammation and a high level of free α-defensins are main features of chronic airway inflammation in alpha-1 antitrypsin-deficient (AATD) individuals. Despite the antimicrobial activities of α-defensins by direct bacterial killing and by modulation of immune responses, AATD individuals are paradoxically burdened by recurrent exacerbation triggered by bacterial infections, frequently with nontypeable Haemophilus influenzae (NTHi). Previous studies demonstrated that high, rather than low α-defensin level could modulate the local pro-inflammatory milieu of bronchial epithelial cells and macrophages promoting chronic inflammation and lower pathogen phagocytosis. IgG-mediated phagocytosis and NTHi adherence, engulfment and phagocytosis were measured in human alveolar macrophages and monocyte-derived macrophages (MDM) isolated from patients with AATD and from healthy individuals. A high concentration of free α-defensins induced NTHi adherence to MDMs but decreased IgG-mediated phagocytosis by MDMs. The decreased phagocytosis was associated with TLR4 activation, downstream signaling via NF-κB p65 and marked increased secretion of inflammatory cytokines, CXCL8, IL-1b, and TNFα by the α-defensin-treated and NTHi-infected MDMs. Exogenous AAT treatment and TLR4 inhibitor decreased TNFα expression in α-defensin-treated cells. Dampening the downstream effects of a high concentration of α-defensins may render AAT and TLR4 inhibitors as potential therapies to decrease NTHi colonization and increase its clearance by phagocytosis in AATD individuals.